Press supervision of local election (Pilkada) transparency in South Sulawesi - Andi Muhammad Farid Fausan Bate; Andi Nurul Istiqamah Bate (Tamalanrea: Journal of Government and Development (JGD), 2024)
This study analyzes the role of press supervision in encouraging transparency and accountability in the implementation of the local elections in South Sulawesi. With a qualitative approach based on literature studies, this study explores how the press contributes to uncovering potential violations, supporting information disclosure, and improving people's political literacy. South Sulawesi, with its complex political dynamics, faces significant challenges in press scrutiny, including political pressure, low media literacy, and the rise of hoaxes. The results show that the press plays an important role as an external supervisor that bridges the government and society, although its effectiveness is often constrained by various factors. Strategic recommendations include strengthening media regulation, increasing public literacy, and cross-sector collaboration to ensure better integrity of the local elections. This research emphasizes the importance of independent media in maintaining the quality of democracy at the local level. This highlights the need for continuous efforts to empower the press as a pillar of democracy, ensuring it remains a reliable watchdog against electoral malpractices and a promoter of informed civic engagement.